Source based Security Issues in WDM Systems - A. Antwiwaa; A. Kumar; A. K Jaiswal (International Journal of Electrical and Computer Engineering (IJECE), 2017)
The issue of security has become a bigger heddle for all telecommunication companies to climb in this era where information hungry customers are increasing daily. Unauthorized users are finding novel ways of accessing information of others and thereby attacking the requisite legitimate users’ information accounting to security threats. In this work, two forms of WDM system attacks will be considered. These attacks include a clone source based attack where the adversary tries to replicate the transmitted signal of the legitimate user by transmitting at the same wavelength and power and the different wavelength source based attack where the adversary transmit at a wavelength different from that of the legitimate user thereby creating interaction effects igniting security issues. Finally, a simulation of the outcome will be considered and the resulting output will be analyzed